RISKS OF INVESTING IN JORDANIAN ISLAMIC BANKS - Al-ashaboul, Mohammad; Al-moumany, Salam (European Scientific Journal, ESJ, 2013)
ï»¿This study aimed to identify the various types of Islamic Finance and how they protect investors and banks from financial risks. To achieve the objectives of this study, the researchers have analyzed the annual reports of the banks work in Jordan, namely, the Jordan Islamic Bank and the Arab Islamic International Bank. The study covers the period between 2007 and 2011. The study found several results, most important, that Islamic banks can avoid the risk through investment methods used, as the study showed that the working capital for Islamic banks during the period of study continues to grow and showed that the return on investment continues to grow, also found, through analysis, that the return on investment for some financial instruments start to decline. Researchers also noted the lack of interest of Islamic Banks Financing Instruments based on the interest rate could lead to miss some investors who prefer to invest using traditional interest rate basis. Based on the results reached, the study found some recommendations. Firstly, the banks can guide investors toward the Islamic financial instruments which maximize the bank returns. Secondly, the researchers advise Islamic Banks to establish more healthy investment environment to activate the other financing instruments which may be important in helping the national economy to grow. Finally, the Islamic banks should also find more financial instruments that combine between the favorable features of traditional and Islamic Financial Instruments to attract more customers who prefer such these financial instruments.